A diagnosis system for detecting cervical lymph node metastasis in oral squamous cell carcinoma: Collective consideration of the results of multiple imaging modalities. Issue 3 (May 2017) - Ishida, Takayuki; Hijioka, Hiroshi; Kume, Kenichi; Yoshimura, Takuya; Miyawaki, Akihiko; Nozoe, Etsuro; Suenaga, Shigeaki; Indo, Hiroko; Majima, Hideyuki J.; Nakamura, Norifumi
Abstract: Object: The aim of this study was to assess our diagnosis system for cervical node metastasis for oral squamous carcinoma (OSCC) based on the combined results of computed tomography (CT), magnetic resonance imaging (MRI), ultrasonography (US), and 18-fluorodeoxyglucose positron emission ( 18 F-FDG-PET/CT). Methods: 106 patients with primary OSCC who underwent surgical treatment were divided into 3 groups. In group 1, cervical node metastasis was diagnosed by disunity combinations of diagnostic devices. In groups 2 and 3, it was assessed according to a set of diagnostic criteria that included the results of the CT/MRI, US and 18 F-FDG-PET/CT. In group 2, node status was considered negative when the results of both CT/MRI and US were negative. In group 3, node status was considered negative when the results of both CT/MRI and US were negative and the maximum standardized uptake value determined via 18 F-FDG-PET/CT was <3.2. Results: 67 patients were diagnosed as cN0. 50 cN0 patients adopted the wait and watch policy, 12 of whom (24.0%) developed cervical node metastasis without recurrence at the primary site. Metastasis rates after surgery improved 33.3%, 23.5%, and 13.3% in groups 1, 2, and 3, respectively. In contrast, positive predict value (PPV) were worst (50.0%, 40.0% and 33.3%). Conclusions: Our diagnosis system reduces the rate of cervical lymph node metastasis after surgery.